Integrated Application-Based Digital Learning Technology in Successful Learning Activities During the Pandemic - Mahsusi Mahsusi; Syihaabul Hudaa; Nuryani Nuryani; Ahmad Bahtiar; Makyun Subuki (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study aimed to look at madrasah's efforts in developing a learning system through